Progress in timing Resistive Plate Chambers - Blanco, A. (2004)
Timing RPCs are Resistive Plate Chambers made with glass and metal electrodes separated by precision spacers. Typical gas gaps are a few hundred micrometers wide. Such counters were introduced in 1999 and have since reached timing accuracies below 50 ps [sigma] with efficiencies above 99% for MIPs. Applications in high-energy physics have already taken place with several more under study.